A Case Report: A Pancreatic Cyst Mask as a Renal Cyst: A Diagnostic Challenge - Mikha Mikha; Putu Angga Risky Raharja (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Pancreatic cysts are increasingly detected and can mimic renal cystic lesions on imaging, particularly on the left side where the pancreatic tail abuts the upper pole of the kidney. Distinguishing between these entities is a diagnostic challenge, as clinical symptoms and standard imaging can be nonspecific. Case. A 55-year-old woman presented with left flank pain, abdominal fullness, nausea, and heartburn. An abdominal CT scan identified a cystic lesion superior to the left kidney, leading to an initial diagnosis of a perirenal cyst. After unsuccessful treatment for GERD, diagnostic retroperitoneoscopy was performed. The intraoperative finding revealed the cyst was not renal but pancreatic origin, necessitating a subsequent open distal pancreatectomy. Conclusion. This case highlights that large pararenal cysts, especially on the left, require pancreatic cysts to be considered in the differential diagnosis. When CT findings are inconclusive, advanced modalities like MRI with tissue-specific contrast or fine-needle aspiration of cyst fluid can be crucial for an accurate preoperative diagnosis and to avoid unnecessary surgical interventions.